Pengaruh Kompetensi dan Pengembangan Karir terhadap Kinerja Pegawai Kantor DISDUKCAPIL Kabupaten Pangkajene dan Kepulauan - Muh. Alam Nasyrah Hanafi; Abdurrahman Hadi; Abdul Hafid Burhami; Nia Ramadhani (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
Employee performance is a crucial factor in the success of any organization, including government agencies. Amidst the increasing demands of public services, employees are required to have adequate competencies and clear career development opportunities to improve performance. This study aims to examine the influence of competency and career development on employee performance at the Population and Civil Registration Office (Disdukcapil) of Pangkajene and Kepulauan Regency. This study used a descriptive method with a quantitative approach. A sample of 86 Disdukcapil employees was drawn using a saturated sampling technique. Data analysis techniques used included validity testing, reliability testing, multiple linear regression analysis, correlation coefficient testing, coefficient of determination testing, t-tests, and F-tests. The results indicate that competency significantly influences employee performance, career development significantly influences employee performance, and competency and career development simultaneously significantly influence employee performance at the Disdukcapil Office of Pangkajene and Kepulauan Regency. This research is expected to be a useful reading material and reference for future researchers who want to examine the influence between competence and career development on employee performance. With the results and findings of this study, it is hoped that future researchers can deepen and expand the study, in addition, it is recommended for future researchers to expand the scope of the research by adding other variables not yet covered in this study, considering that there is still around 24% of the influence on employee performance that cannot be explained by the variables used.